Reduced CD4+,CD25- T cell sensitivity to the suppressive function of CD4+,CD25high,CD127-/low regulatory T cells in patients with active systemic lupus erythematosus - Venigalla, Ram Kumar Chowdary; Tretter, Theresa; Krienke, Stefan; Max, Regina; Eckstein, Volker; Blank, Norbert; Fiehn, Christoph; Ho, Anthony Dick; Lorenz, Hanns-Martin (Arthritis & rheumatism, 2008)
Objective CD4+,CD25high regulatory T (Treg) cells play a crucial role in the maintenance of self tolerance and prevention of organ-specific autoimmunity. The presence of many in vivo-preactivated CD4+,CD25++ T cells in patients with systemic lupus erythematosus (SLE) poses a difficulty in discriminating CD25++ activated T cells from CD25high Treg cells. To overcome this problem, we analyzed the phenotype and function of CD4+,CD25high,CD127−/low natural Treg (nTreg) cells isolated from the peripheral blood of patients with SLE. Methods CD4+,CD25high,CD127−/low nTreg cells and CD4+,CD25− responder T (Tresp) cells from patients with SLE and normal donors were separated by fluorescence-activated cell sorting. Cell proliferation was quantified by 3H-thymidine incorporation, and immunophenotyping of the cells was done using FACScan. Results Comparable percentages of CD4+,CD25high,FoxP3+ T cells were observed in patients with SLE and normal donors. Proliferation of SLE nTreg cells sorted into the subset CD4+,CD25high,CD127−/low was significantly decreased compared with that of SLE nTreg cells sorted into the subset CD4+,CD25high (mean ± SEM 2,223 ± 351 counts per minute versus 9,104 ± 1,720 cpm, respectively), while in normal donors, these values were 802 ± 177 cpm and 2,028 ± 548 cpm, respectively, confirming that effector cell contamination was reduced. Notably, the suppressive activity of nTreg cells was intact in all groups. However, CD4+,CD25− Tresp cells isolated from patients with active SLE were significantly less sensitive than those from patients with inactive SLE to the suppressive function of autologous or normal donor CD4+,CD25high,CD127−/low nTreg cells. Furthermore, a significant inverse correlation was observed between the extent of T cell regulation in suppressor assays and the level of lupus disease activity. Conclusion This study is the first to show that, in human SLE, impaired sensitivity of Tresp cells to the suppressive effects of a comparably functional, highly purified nTreg cell population leads to a defective suppression of T cell proliferation in active SLE. Studies aiming to define the mechanisms leading to Tresp cell resistance might help in the development of highly specific, alternative immunotherapeutic tools for the control of systemic autoimmune diseases such as SLE.
Im Titel sind in "CD25high,CD127-/low" die Begriffe "high" und "-/low" hochgestellt
Gesehen am 07.10.2021